Manajemen Digitalisasi Pengarsipan Perpustakaan - Akhsani Taqwiym (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2025)
Archiving digitization has become an urgent need for libraries to address the increasing volume of documents and the need for fast and accurate information services. This study aims to develop an archiving digitization management system at XYZ Library as a solution to the previously manual and time-consuming process of recording and retrieval of archives. The methodology used adopts a waterfall model that includes the stages of needs analysis, workflow design, web-based system implementation, function verification, and maintenance. Data collection was conducted through direct observation, in-depth interviews, and documentation of the archiving process. The results show that the use case design and Data Flow Diagram (DFD) are able to describe an integrated workflow from the departmental data input process, recording sender identities, uploading digital archives, to storage in the database. The interface implementation is designed to facilitate staff in managing archives systematically, quickly, and securely. In conclusion, the developed E-Archive system provides significant improvements in operational efficiency, data collection accuracy, and document accessibility in the library. These findings confirm that digitization is a crucial element in building modern library governance that is sustainable and responsive to information needs.